DESENVOLVIMENTO DE SENSORES A PARTIR DE FILMES DE ÓXIDO DE GRAFENO FOTORREDUZIDOS APLICÁVEIS À LÍNGUA ELETRÔNICA - CAIO ROCHA NUNES REIS (2021)
The development of research and technological applications that are somehow based on the working mechanism of at least one of the five human senses has its origins in the 1940s. However, it was only after 1993 that it was possible to develop the first models of electronic language: devices inspired by the human taste, equipped with sensors with high selectivity capable of producing unique electrical signatures for each substance analyzed with the help of some mathematical analysis method that facilitates pattern recognition. In this work, a potential sensor for electronic tongue was developed using laser reduced graphene oxide films and the Principal Component Analysis (PCA). Five solvents (DI-water, ethanol, ethylene glycol, dimethylformamide and acetone) were used to study the efficiency of the sensor and help to understand the physical-chemical mechanisms involved in the transduction process. In addition to solvents, the sensors proved to be efficient in separating samples of absolute and adulterated ethanol.